ANALYSIS OF THE EVOLUTION AND CURRENT STATUS OF THE AUSTRIAN CIVIL PROCEDURAL LAW - Salma, Marija (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
The paper analyses the rules contained in the Austrian Civil Procedure Act. Although this act was adopted back in 1895, it is still in force. This continuity is a proof of the great value of this legislative document. This Act has had a significant influence on the Central and Eastern European procedural laws. From the period of its enactment, despite preserving its fundamental components, the Austrian Civil Procedure Act has been through a number of modifications, including the amendments that were introduced towards the end of 20th and in early 21st century. More recent modifications are a result of the influence of common European procedural law and concern the issues like jurisdiction, enforcement of decisions, proceedings concerning payment orders, special litigations, non-contentious proceedings. The Austrian civil procedural law, as a normative system, accompanied by a rich literature and creative judicial practice, has influenced the Serbian law, whose system and particular institutes have accepted the solutions contained in the Austrian law. The paper gives an overview of the systems and basic institutes of the Austrian civil procedure: complaint, response to the complaint, preliminary hearing, main hearing, evidence and evidentiary hearing, court’s ruling. The aim is to consider the existing contents of the Austrian Civil Procedure Act in the context of reforms of the Serbian Civil Procedure Act.